Does autosomal dominant polycystic kidney disease increase the risk of aortic aneurysm or dissection: a point of view based on a systematic review and meta-analysis - Nunes, Raquel (2022)
© The Author(s) under exclusive licence to Italian Society of Nephrology 2022